The Relationship of Central Pedestrian Paths on Suroto Street, Kotabaru with Ebenezer Howard’s Garden City Concept - Titi Ajeng Wulandari; Rony Gunawan Sunaryo; Trias Mahendarto (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2026)
The Kotabaru area of Yogyakarta is a heritage district originally designed based on the garden city concept and has undergone functional transformations over time. The revitalization of the central pedestrian path on Suroto Street in 2018 altered the quality of public space, raising issues related to pedestrian safety, comfort, and connectivity. The research problem is the extent to which the pedestrian path remains relevant to garden city principles and meets contemporary walkability standards. The purpose of this study is to evaluate the relationship between the central pedestrian path on Suroto Street and garden city principles from morphological, ecological, and pedestrian safety perspectives. A qualitative descriptive-comparative method was employed through field observations, visual documentation, and literature review. The findings indicate that the visual character and boulevard vegetation are preserved; however, aspects of safety, path continuity, crossing visibility, and ecological connectivity remain suboptimal. The novelty of this study lies in integrating historical-morphological analysis of the heritage area with technical walkability assessment. This study contributes to developing adaptive design recommendations that support heritage conservation while enhancing pedestrian quality and safety. The research is limited to four pedestrian segments, focusing on existing conditions.